2012
DOI: 10.1371/journal.pone.0047963
|View full text |Cite
|
Sign up to set email alerts
|

A Simple State-Determined Model Reproduces Entrainment and Phase-Locking of Human Walking

Abstract: Theoretical studies and robotic experiments have shown that asymptotically stable periodic walking may emerge from nonlinear limit-cycle oscillators in the neuro-mechanical periphery. We recently reported entrainment of human gait to periodic mechanical perturbations with two essential features: 1) entrainment occurred only when the perturbation period was close to the original (preferred) walking period, and 2) entrainment was always accompanied by phase locking so that the perturbation occurred at the end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 43 publications
3
48
0
Order By: Relevance
“…Fourteen subjects [5 females, 9 males; mean age = 18.7 (18)(19)(20)(21) years] participated in experiment 1, 18 subjects [7 females, 11 males; mean age = 19.1 (18)(19)(20)(21) years] participated in experiment 2, and 12 subjects [5 females, 7 males; mean age = 20.0 (18)(19)(20)(21)(22) years] participated in experiment 3. Data from two subjects in experiment 1 were excluded because their average stepping accuracy across all conditions was more than 2 SDs from the mean.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen subjects [5 females, 9 males; mean age = 18.7 (18)(19)(20)(21) years] participated in experiment 1, 18 subjects [7 females, 11 males; mean age = 19.1 (18)(19)(20)(21) years] participated in experiment 2, and 12 subjects [5 females, 7 males; mean age = 20.0 (18)(19)(20)(21)(22) years] participated in experiment 3. Data from two subjects in experiment 1 were excluded because their average stepping accuracy across all conditions was more than 2 SDs from the mean.…”
Section: Methodsmentioning
confidence: 99%
“…As such, a small forward perturbation applied to the COM at midstep increases the speed of the COM, which in turn increases the collision loss so the additional energy that is injected into the system by the perturbation will be dissipated at collision (15). Although the basin of attraction for bipedal gait may be relatively shallow, spinal-level reflex pathways (3) may serve to facilitate gait-restorative responses that take advantage of this passive stability (18)(19)(20). † Active Control of Walking These insights imply that certain desirable characteristics of movement, such as coordination, efficiency, and stability, can emerge without active (i.e., perceptually guided) control.…”
Section: Significancementioning
confidence: 99%
“…Consistent with mathematical models, the energy dissipation due to non-elastic foot-ground interaction during the heel strike may be an essential element of legged locomotion rather than an accidental imperfection (Ahn & Hogan, 2012). It may not only provide indispensable sensory cues from foot contact of the leading leg (reflecting cutaneous input or load -related afferents) to coordinate locomotor patterns, but may also be a key mechanical factor that determines the stability of locomotion (Ahn & Hogan, 2012) as medio-lateral stability is mainly ensured by foot placement ('stepping strategy') (Hof, Vermerris, & Gjaltema, 2010). The importance of double support phase is also linked to the relation between postural stability, interlimb coordination and the metabolic cost of walking (Donelan, Shipman, Kram, & Kuo, 2004;Holt, Jeng, Ratcliffe, & Hamill, 1995;Krasovsky et al, 2012).…”
Section: Gait Asymmetry and Interlimb Coordination Impairment In Subjmentioning
confidence: 77%
“…According to motor control theories, the system adjusts muscle activation thresholds of the trailing limb to guarantee dynamic gait stability (Feldman, Krasovsky, Baniña, Lamontagne, & Levin, 2011). Consistent with mathematical models, the energy dissipation due to non-elastic foot-ground interaction during the heel strike may be an essential element of legged locomotion rather than an accidental imperfection (Ahn & Hogan, 2012). It may not only provide indispensable sensory cues from foot contact of the leading leg (reflecting cutaneous input or load -related afferents) to coordinate locomotor patterns, but may also be a key mechanical factor that determines the stability of locomotion (Ahn & Hogan, 2012) as medio-lateral stability is mainly ensured by foot placement ('stepping strategy') (Hof, Vermerris, & Gjaltema, 2010).…”
Section: Gait Asymmetry and Interlimb Coordination Impairment In Subjmentioning
confidence: 94%
“…Taga proposed a control paradigm for walking based on the entrainment of neural oscillators (famously known as Central Pattern Generation - CPG) [22], which has been the basis of numerous works on locomotion control ever since [23]. Although the role of CPG in human walking remains a point of contention [24], Ahn and Hogan showed that the frequency of walking in healthy subjects adapts itself to rhythmic pulses from an external actuator on the ankle [25]. The small basin of entrainment observed in their experiments can be attributed to characteristics of a stable nonlinear oscillator underlying human walking.…”
Section: Entrainment and Application In The Control Of Active Prosthementioning
confidence: 99%